2011
DOI: 10.3109/0886022x.2011.599911
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Acute Kidney Injury after Exposure to Gadolinium-Based Contrast in Patients with Renal Impairment

Abstract: Objectives: Gadolinium-based contrast media (Gd-CM) are reported to induce acute kidney injury (AKI) in a high-risk population group at the usual dose for magnetic resonance imaging (MRI) and magnetic resonance angiography (MRA) examinations. We assessed gadolinium-induced nephropathy in patients with renal impairment who underwent MRI or MRA examinations, and evaluated the risk factors. Materials and methods: In this retrospective study, 238 patients with baseline renal impairment, who received MRI or MRA exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 27 publications
0
21
0
2
Order By: Relevance
“…In the other four studies [1720] in which GBCA-related nephrotoxicity was reported in CKD patients, two studies [17, 18] also reported a higher CIN rate (50 % and 28 %, respectively). Compared to RESCUE, CIN occurred in populations with similar degrees of CKD, but with globally smaller number of patients (10 [17] and 25 [18]), definitions of CIN that did not strictly comply with ESUR guidelines—more than 50 % decrease in GFR [17], at least 44.2 μmol/l (0.5 mg/dl) increase of baseline serum creatinine levels at 48 h, or need for dialysis within 5 days [18]—and high doses of CM: 0.57 ± 0.17 mmol/kg [17] or 0.6 ± 0.3 mmol/kg [18] for angiographic examinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the other four studies [1720] in which GBCA-related nephrotoxicity was reported in CKD patients, two studies [17, 18] also reported a higher CIN rate (50 % and 28 %, respectively). Compared to RESCUE, CIN occurred in populations with similar degrees of CKD, but with globally smaller number of patients (10 [17] and 25 [18]), definitions of CIN that did not strictly comply with ESUR guidelines—more than 50 % decrease in GFR [17], at least 44.2 μmol/l (0.5 mg/dl) increase of baseline serum creatinine levels at 48 h, or need for dialysis within 5 days [18]—and high doses of CM: 0.57 ± 0.17 mmol/kg [17] or 0.6 ± 0.3 mmol/kg [18] for angiographic examinations.…”
Section: Discussionmentioning
confidence: 99%
“…This could at least partly explain the higher CIN rates compared to that observed with Gd-DOTA alone, although a number of published studies have also shown that administration of these GBCAs is associated with no or a low rate of CIN in CKD patients [35] and have even reported a serum creatinine level decrease after the administration of gadolinium [21]. In the remaining two studies [19, 20], conducted with some of these GBCAs, lower CIN rates were observed: 1.9 % [19] and 2.5 % [20]. The differences with RESCUE, despite higher doses of GBCAs, were either a more stringent definition of CIN (at least 1.0 mg/dl increase in baseline serum creatinine levels at 48 h and oligoanuria [19]) in a similar CKD population (mean baseline creatinine clearance: 38.2 ± 16 ml/min) [19] or a less severe CKD population (46.8 % of patients with mild CKD) with a different CIN definition (greater than 25 % decrease of baseline GFR) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Without a more robust strategy, such articles relevant to the care of dialysis patients would be missed in clinicians' searches. On the other hand, some articles mention dialysis patients, but only as an exclusion criterion (i.e., patients receiving maintenance dialysis were excluded from trial participation) (20)(21)(22). Other articles may mention that patients are not yet undergoing dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, however, a severe reaction known as nephrogenic systemic fibrosis was reported in patients treated with GDBCAs (Thomsen, 2006;Thomsen et al, 2007;Chien et al, 2011;Bernstein et al, 2012;Chang et al, 2013). Thus, the diagnostic use of GDBCAs is currently managed with the caution of preventing severe renal complications (Edwards et al, 2014).…”
Section: Ree Iatrogenic Exposuresmentioning
confidence: 97%
“…Non-occupational, environmental REE exposures have been reported by a few studies of populations residing in REE mining areas that reported REE accumulation as related to distance from mining areas (Peng et al, 2003;Tong et al, 2004), or associated REE exposure with changes in serologic endpoints (Zhu et al, 2005). A recognized iatrogenic exposure consists of gadolinium (Gd) use as a contrast agent in magnetic resonance imaging, up to reports on renal toxicity (nephrogenic systemic fibrosis) in the last decade (Thomsen, 2006;Chien et al, 2011;Bernstein et al, 2012).…”
Section: Introductionmentioning
confidence: 96%